The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1242/dev.162016
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous fates and dynamic rearrangement of regenerative epidermis-derived cells during zebrafish fin regeneration

Abstract: The regenerative epidermis (RE) is a specialized tissue that plays an essential role in tissue regeneration. However, the fate of the RE during and after regeneration is unknown. In this study, we performed Cre--mediated cell fate tracking and revealed the fates of a major population of the RE cells that express () during zebrafish fin regeneration. Our study showed that these RE cells are mainly recruited from the inter-ray epidermis, and that they follow heterogeneous cell fates. Early recruited cells contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Zebrafish fin ray branching provides an accessible context to define mechanisms of appendage patterning and skeletal morphogenesis. Our current and earlier study (Armstrong et al, 2017) The directly observed distal movement and likely shedding of fins' basal epidermis, as previously surmised during regeneration (Armstrong et al, 2017;Shibata et al, 2018) is intriguing both functionally and mechanistically. Functionally, continuous bEp replacement may enable rapid recovery from frequent environmental insults.…”
Section: Basal Epidermal Movements and Shh/smo Signaling Direct Skelesupporting
confidence: 74%
“…Zebrafish fin ray branching provides an accessible context to define mechanisms of appendage patterning and skeletal morphogenesis. Our current and earlier study (Armstrong et al, 2017) The directly observed distal movement and likely shedding of fins' basal epidermis, as previously surmised during regeneration (Armstrong et al, 2017;Shibata et al, 2018) is intriguing both functionally and mechanistically. Functionally, continuous bEp replacement may enable rapid recovery from frequent environmental insults.…”
Section: Basal Epidermal Movements and Shh/smo Signaling Direct Skelesupporting
confidence: 74%
“…3A and fig. S1B) (15,16). By integrating cells from all stages during regeneration, we found clusters of cells that corresponded to all three layers of the epithelium after injury (Fig.…”
Section: Diverse Epithelial Populations Are Involved In Regenerationmentioning
confidence: 94%
“…Epithelial cells are from three transcriptionally distinct subgroups, representing the superficial (krt4), intermediate (tp63), and basal layers (tp63 and krtt1c19e) of the epithelium (fig. S1, A and B) (15,16).…”
Section: Regenerating Fins Comprise the Same Cell Types As Uninjured mentioning
confidence: 99%
“…In addition to the recruitment of neutrophils and macrophages, one of the earliest responses to the injury is the migration of epithelial cells, which form an epithelium covering the wound (Figure 2a) (Poleo, Brown, Laforest, & Akimenko, 2001;Shibata, Ando, Murase, & Kawakami, 2018). Within the next hours to days, the epithelium becomes a multilayered structure, termed the wound or regeneration epidermis (Chen et al, 2015;Shibata, Ando, et al, 2018). In contrast to mammalian limb injury, which is associated with local tissue degradation (Simkin et al, 2015), in zebrafish the regeneration process starts immediately after wound closure.…”
Section: Caudal Fin Regenerationmentioning
confidence: 99%